(untitled) (World Bulletin of Public Health, 2024)
A jaw fracture, like other fractures, is a severe injury requiring immediate treatment. The fracture violates the integrity of not only the bone, but also the surrounding tissues, blood vessels, muscle structures and nerves. In addition, a jaw fracture is often accompanied by displacement of bone structures and fragments, which entails serious consequences in case of late initiation of treatment. The proximity of the location to the brain and the large number of blood vessels in this area makes this type of injury life-threatening.